Clinical Application and Psychometric Properties of a Swedish Translation of the Abbreviated Profile of Hearing Aid Benefit - Brännström, K. Jonas; Andersson, Ketty; Sandgren, Olof; Whitling, Susanna (Journal of the American Academy of Audiology, 2020)
Background The impact of hearing loss on the individual and his/her everyday life can be assessed using questionnaires with the purpose to improve rehabilitation quality. The Abbreviated Profile of Hearing Aid Benefit (APHAB) can be used to evaluate disability in everyday life associated with hearing loss. Previous studies have examined APHAB outcomes in sensorineural hearing loss and we do not know whether the type of hearing loss influence questionnaire outcomes.Purpose The purpose was to evaluate the psychometric properties of a Swedish translation of the APHAB and the influence of demographic variables on the outcome in a clinical sample.Research Design A descriptive, cross-sectional study in a clinical sample.Study Sample Forty-eight participants with no hearing aid experience seeking audiological rehabilitation for the first time. These participants represented different degrees of hearing loss and three types of hearing loss: monaural mixed, binaural mixed, and binaural sensorineural hearing loss.Data Collection and Analysis Pure-tone audiometry was conducted and the participants completed the unaided APHAB during their first appointment at the clinic. Psychometric properties of the questionnaire were examined and the influence of age, gender, type of hearing loss, and degree of hearing loss on APHAB scores were studied.Results The psychometric properties indicate high test-retest reliability but there seems to be some potential issues with the properties of the reverberation (RV) subscale. The items from the RV subscale failed to load as a separate component and the internal consistency of the subscale improved by removing four items (items 1, 9, 11, and 16). With few exceptions, APHAB scores were not influenced by age, gender, or type of hearing loss. APHAB scores were generally influenced by degree of hearing loss in both the best and the worst ear.Conclusion This Swedish version of the APHAB can be additionally improved by addressing the inconsistencies found in the RV subscale by rephrasing or removing some items. The degree of hearing loss has some influence on questionnaire outcomes but not age, gender, and type of hearing loss.
Keywords: questionnaires; auditory rehabilitation; first time